Modelo de especificação de interfaces tangíveis de mesa - TTUI-SM - Dourado, Antonio Miguel Batista (Universidade Federal de São Carlos, 2012)
In the scenario of computational interfaces development, researches efforts aim to offer new ways of interaction that are closer to the natural way which humans interact with the real world. Amongst the diversity of interface modalities, the tabletop tangible interfaces make the link between physical objects and virtual objects, making possible to "grasp" the interface and interact with it physically, also counting on multitouch interactions. However, in the development process of this kind of interface, there is a lack of specification s model that supports, not only the physical objects interaction, but multitouch interactions as well, and that organizes and classifies the specification in a more agile manner, easier to document and implement. Thus, this work presents a new tabletop tangible user interface specification model, TTUI-SM, that classifies and organizes the interface element specification within many components. A diagramatic tool, TTUI-SMT, was developed based on this model, aiming to make the interface specification and development faster, easier and automatized. To validate the model and tool, two studycases were introduced and specified. An experiment was conducted to evaluate both model and tool, resulting in the comprovation, through questionnaires analysis, of the proposed benefits.
Keywords: Interfaces de usuário; Interação homem-máquina; Especificação formal; Interfaces tangíveis; Desenvolvimento de Interfaces Tangíveis; Tangible Interfaces; Tabletop User Interfaces; Computer-Human Interface; Tabletop Tangible Interface Specification; Tangible Interface Development; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO